Are Atypical Things More Popular? - Berger, Jonah; Packard, Grant (Psychological Science, 2018)
Why do some cultural items become popular? Although some researchers have argued that success is random, we suggest that how similar items are to each other plays an important role. Using natural language processing of thousands of songs, we examined the relationship between lyrical differentiation (i.e., atypicality) and song popularity. Results indicated that the more different a song’s lyrics are from its genre, the more popular it becomes. This relationship is weaker in genres where lyrics matter less (e.g., dance) or where differentiation matters less (e.g., pop) and occurs for lyrical topics but not style. The results shed light on cultural dynamics, why things become popular, and the psychological foundations of culture more broadly.